P‐89: Diffraction Simulation of Camera Under LCD Considering the Influence of Liquid‐Crystal Phase Modulation. Issue 1 (28th June 2021) - Deng, Qian; Zhu, Jiuhui; Hou, Shaojun; Huang, Changchih; Wang, Chao; Liu, Guanghui; Li, Zhifu
Abstract : In this paper, we propose a simulation method to evaluate the diffraction when capturing through a LCD panel, taking the LC retardation factor into account, and figure out calculated diffraction images matching well with actually captured ones. The influence of pixel design, transmittance distribution function, and phase distribution function on diffraction are discussed in detail. Distinguishing the contribution of the above factors on diffraction can further pave the way to imaging quality improvement of LCD‐based Camera‐Under‐Panel (CUP) application.